Constraint of accessible chromatins maps regulatory loci involved in maize speciation and domestication - Yuting Liu; Xiang Gao; Hongjun Liu; Xuerong Yang; Xiao Liu; Fang Xu; Yuzhi Zhu; Qingyun Li; Liangliang Huang; Fang Yang; Jinsheng Lai; Junpeng Shi (Nature Communications)
Abstract Comparative genomic studies can identify genes under evolutionary constraint or specialized for trait innovation. Growing evidence suggests that evolutionary constraint also acts on non-coding regulatory sequences, exerting significant impacts on fitness-related traits, although it has yet to be thoroughly explored in plants. Using the assay for transposase-accessible chromatin by sequencing (ATAC-seq), we profile over 80,000 maize accessible chromatin regions (ACRs), revealing that ACRs evolve faster than coding genes, with about one-third being maize-specific and regulating genes associated with speciation. We highlight the role of transposable elements (TEs) in driving intraspecific innovation of ACRs and identify hundreds of candidate ACRs potentially involved in transcriptional rewiring during maize domestication. Additionally, we demonstrate the importance of accessible chromatin in maintaining subgenome dominance and controlling complex trait variations. This study establishes a framework for analyzing the evolutionary trajectory of plant regulatory sequences and offers candidate loci for downstream exploration and application in maize breeding.